Harmonisation of Old-Age Security Within the European Union - Silke Uebelmesser (Center for Economic Studies and ifo Institute (CESifo), 2003)
Not sufficiently harmonised national pension systems within the European Union distort the allocation of labour and endanger redistributive activities. This paper identifies the most decentralised level of harmonisation which guarantees efficient allocation and enables redistribution. For this, we build on theoretical results to evaluate the realised distribution of the legal power between the European Union and the Member States and the resulting level of harmonisation. We find that harmonisation is sub-optimally low. Binding rules guaranteed by the European Union are needed which means that the Member States have to concede more fundamental responsibilities to the European Union.
Keywords: 330; European integration; mobility; unfunded pension systems; system competition; allocation of labour; intergenerational redistribution